Risk Factors For Type 2 Diabetes Mellitus Patients At The Monano Health Center, North Gorontalo District - Dungga, Elvie Febriani; Indiarti, Yuni (Jambura Nursing Journal, 2024)
Diabetes Mellitus is a non-communicable disease that contributes to at least 70% of deaths in the world. This is proven by the International Diabetes Federation (IDF) report which states that the number of people suffering from type 2 diabetes mellitus is increasing every year. The general aim of this research is to determine risk factors that can be modified and cannot be modified in Type 2 Diabetes Mellitus patients at the Monano Community Health Center, North Gorontalo Regency in 2023. This research was conducted from July to August 2023 with this type of research being descriptive analytical with data analysis. univariate. In this research, the instrument used was a questionnaire containing questions using language that had been changed by the researcher into language that was easy for the respondent to understand and an observation sheet filled in by the researcher. The results of the study showed that the highest frequency of obesity was in Normal status, namely 16 (51.6%), the highest frequency of physical activity in low activity was 20 (64.5%), the highest frequency of patients who did not have hypertension was 23 (74.2%), the highest frequency of patients namely experiencing dyslipidemia, namely 17 (54.8%), the highest frequency of patients, namely poor eating patterns, namely 24 (77.4%), the highest frequency of patients, namely patients who do not smoke, namely 28 (90.3%), and the highest frequency of patients who do not consume alcohol, namely as many as 31 (100.0%). There is a need for further research regarding the factors that influence blood sugar control in patients with type 2 diabetes mellitus.